Blockchain based solution for secure information sharing in pharma supply chain management - Adla Padma; Mangayarkarasi Ramaiah (Heliyon)
Pharmaceutical supply chain management (PSCM) aims to alleviate logistical challenges. However, traditional online pharma systems face issues during implementation, particularly regarding transparency and fostering mutual trust among stakeholders. The primary security goals for a supply chain management (SCM) solution are ensuring authentication, confidentiality, data provenance, and auditability. The proposed blockchain-based solution (BPSCM) is implemented in three phases: registration, pharmaceutical product circulation, and secure payment. The registration phase computes the identification number upon the hashed private key along with the Edwards-curve digital signature algorithm (EdDSA) for all the stakeholders. The pharm product circulation phase implements the transactions among the participants by developing smart contracts where cryptographic operators ensure data provenance. The security analysis demonstrates that the framework effectively mitigates impersonation and collusion attacks. Performance metrics, including gas consumption, throughput, latency, and computational cost, were examined and compared to standard PSCM frameworks to evaluate the BPSCM's effectiveness.